Pengaruh Gaya Kepemimpinan Demokratis Terhadap Pemberdayaan Psikologis Karyawan: Literature Review - Khumaira, Lubbi Atika; Muhid, Abdul (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
The ideas used in improving a company come from its human resources. Employees are a source of human energy that holds an important position in the implementation of the vision, mission, and objectives of an industry. Employee performance as one of the markers that need to be noticed by the company. When employees are dissatisfied and there is a loss in their performance, it will be able to limit the performance of the company. One of the triggers that can affect the employee's work environment is from the leader. There are various styles of leadership favored by employees, one of which is the democratic leadership style. This research was conducted to recognize the influence of democratic leadership style on the psychological empowerment of employees. The research method used is a library study procedure or literature review. The information used in this study, taken from various scientific journals, scientific articles, and books related to research variables. The results showed that democratic leadership style is able to influence the psychological empowerment of employees. The style of democratic leadership can influence the psychological empowerment of employees because employees are actively involved so that they feel the meaning, self-determination, impact, and competence in work.